Development of Hyper-Content E-Modules for the “Script and Storyboard” Course Based on Project-Based Learning - Agus Hadi Utama; Qomario Rio; Brezto Asagi Dewantara; Abdul Rahman (STKIP Al Islam Tunas Bangsa dan HEPI, 2026)
The transformation of digital education demands innovative learning resources to foster student independence. This study aims to develop and test the feasibility of a Hyper content E-Module based on Project Based Learning (PjBL) in the Script and Storyboard course to overcome the limitations of teaching materials and increase learning independence. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection was carried out through validation questionnaires from media and material experts, as well as questionnaires on student independence and reflection on learning experiences. The results showed that the developed E-Module was categorized as